Confronting Cybersecurity Challenges through US-Singapore Partnership - Hung, Harry (2016)
Cyber cooperation remains a prominent area of mutual interest between Singapore and Washington. Singapore’s Cyber Security Agency (CSA) and the US Department of Homeland Security (DHS) recently established a formal cybersecurity partnership. This agreement will improve bilateral cybersecurity and potentially create mechanisms for ASEAN nations to better address cybersecurity challenges.